Creative Chemistry Teaching - JAHANGIRI, M.; HAJIAN , R. (Asian Journal of Chemistry, 2012)
In the present paper, a strong call is issued to reconsider the teaching methods used by teachers in general and chemistry teachers in particular. The study makes an attempt to derive the widely-applicable and practical teaching procedures so as to logically indicate the probabilistic directions in which chemistry teaching has to proceed. For this purpose, specific reference is made to the notions of creativity and problem-solving and the fact that true learning is deeply rooted in these psychological concepts. In the end, creativity is redefined and its critical role, which has often been ignored, is reincorporated in the teaching profession. Specific guidelines are presented to introduce this psychological concept in chemistry classes